Freud’s View of Religion in Moses and Monotheism - Hasanova, Nargizkhatun (Scholarya Demo Journal of Ruby, 2018)
The article is presented to the reader, taking into account some nuances. It analyzes Freud’s attitude towards religion, its origin, position in human psychology and society as a whole. Thus, the objective of the study is Z. Freud, his psychoanalytic theory and religion. In order to comprehensively bring the nature of this relationship to the attention of the reader, the article presents various nuances, covering Freud’s contributions to psychology and the theory of religion.The facts from Freud’s life are briefly summarized in the study for understating his reasons of negative attitude towards religion. It was also affected by the religious and living conditions of his place of residence. The article also reflects information about his scientific activities, as well as information about famous scientists of his period, whose thoughts influenced him. The book Moses and Monotheism was not chosen by chance. Many researchers considered this work to be a continuation of Totem and Taboo. Many nuances deserve attention in this book. S. Freud’s view of history in this work is also different. He applied psychoanalysis to some historical facts. As a result, many different opinions have arisen. For this reason, there are many differences between historical Moses with the image described by S. Freud in the book. The main goal of the article is not to determine the authenticity or erroneousness of these views, but in general, to see the connection between religion and psychoanalysis in the style presented by Freud. In order to partially comprehend these thoughts, it is necessary to correctly understand the theory of psychoanalysis and the terms that constitute its basis. Thus, the article attempts to objectively identify psychoanalytic theory of Freud.